THE EFFECT OF YOUTUBE EDUCATIONAL CHANNEL ON STUDENTS’ LISTENING COMPREHENSION AT SMAN 8 LUWU TIMUR - Astuty, Ratri Septi; Muliati, Andi; Muhayyang, Maemuna (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The objective of this study was to determine the effect of  YouTube   educational channel   on   students’   listening   comprehension. This research  method   was   Pre- experimental design.  The  population  of  this  research  was  the  eleventh  grade  students of SMAN 8 Luwu Timur in the academic year 2022/2023 through a random sampling technique.   The   sample   of   this   research   is   30   students   from   XI   MIPA   1.   The instrument  of  this research was listening test,  which delivered as the pretest  and the post-test.  The  research  findings  showed  that  using  YouTube  educational  channel  in learning listening was significant  to improve students’  listening comprehension.  It  was proved  that  the  mean  score  of  students’  pretest  was  64.17  and  the  mean  score  of students’  posttest  was  85.17.  From  that  data,  it  could  be  concluded  that  the  use  of YouTube  educational  channel  could  improve  students’  listening  comprehension. Keywords— YouTube Educational Channel, Listening Comprehension